ENERGY-SAVING MATERIALS FOR ELECTRICAL ENGINEERING - Berdiev U. T.; Sulaymonov U. B.; Hasanov F. F.; Karshiyev K. T. (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the issue of widespread introduction with a high specific consumption of magnetic materials in the production of micromachines; a very promising direction is the development of a waste-free technology for the manufacture of magnetic cores and cores using powder metallurgy methods. The use of soft magnetic materials obtained by powder metallurgy methods allows reducing the loss of electrical steel and eliminating many labor-intensive operations, automating the technological process and ensuring the required dimensional accuracy of parts, excluding further finishing machining. Using soft magnetic materials for the construction of electrical machines, it is possible to obtain a sufficiently high value of the efficiency and reduce the losses due to hysteresis.